(untitled) (Biomedical Research and Therapy, 2018)
Cardiac disease is the second common cause of syncope in emergency departments. Patients with Cardiac syncope have a higher risk of mortality than those who have a non-cardiac problem. Brain natriuretic peptide (BNP) as a cardiac marker has not thoroughly been evaluated in patients with syncope. This article focuses on the studies that have assessed BNP and NT-pro-BNP in cardiac and non-cardiac syncope patients in emergency departments.